Development of RLC Circuit Modelling for Simulation of Stator Winding Frequency Response using Genetic Algorithm - Che Ku Abu Bakar, Nur Ainaa Amirah; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2022)
The induction motor is one of the AC motors commonly used in the industry as it comes with excellent advantages. AC motor can run as a single-phase induction motor (SPIM) or a three-phase induction motor (TPIM). This TPIM motor is the most frequently used in many industries due to its excellent features. However, TPIM can be prone to electrical faults that lead to stator faults. Therefore, the condition assessment of the motors has drawn considerable attention to keep the operation running smoothly. Frequency Response Analysis (FRA) can be used to determine the state of the stator winding. This method was previously only utilized to analyze the frequency response of power transformers. The FRA method is the most effective for detecting motor failure or damage as a reference for evaluating the measured response. An RLC circuit model is developed using MATLAB/Simulink to simulate the frequency response of the stator winding. The response from the RLC circuit model will then be compared with the actual measurement. The Genetic Algorithm (GA) improves the simulated response to get the precise and accurate parameters for each element to minimize the response error.